Induction of lymphangiogenesis in and around axillary lymph node metastases of patients with breast cancer - Van den Eynden, G G (Nature Publishing Group, 2006)
We studied the presence of lymphangiogenesis in lymph node (LN) metastases of breast cancer. Lymph vessels were present in 52 of 61 (85.2%) metastatically involved LNs vs 26 of 104 (25.0%) uninvolved LNs (P<0.001). Furthermore, median intra- and perinodal lymphatic endothelial cell proliferation fractions were higher in metastatically involved LNs (P<0.001). This is the first report demonstrating lymphangiogenesis in LN metastases of cancer in general and breast cancer in particular.